Body Image and HIV: Exploring the Stories of HIV-Positive Women - Gibson, Michelle V. (My University, 2011)
This study explored the relationship that HIV-positive women have constructed with their bodies both pre-HIV and post-HIV diagnosis. The research was based on feminist and postmodernist theoretical perspectives and narrative based qualitative interviews with six HIV-positive women residing in Ontario. The women’s narratives formed the basis of the data analysis. The findings revealed stories of women’s complex relationships with their bodies that were influenced by cultural discourse of the female body, change to their bodies post-HIV, side effects of HIV medications, a yearning to change their bodies with cosmetic procedures, and HIV-related stigma. While women’s stories illustrated reflections from the past and present, their stories also moved non-linearly through time. These stories challenged the idea of a grand truth about how women experience their bodies and suggested women’s relationship with their bodies is an active and fluid process. The theoretical perspectives of this research and the stories of HIV-positive women provided implications for future social work practice and research. Feminist and postmodern approaches are encouraged in future research and practice to promote non-silencing and non-pathologizing experiences for HIV-positive women. The stories shared by women suggested that the dominant model of female beauty affects the relationship constructed with their bodies and shapes the lives of women both pre-HIV and post-HIV diagnosis. These stories validated that body image concerns are indeed present in women living with HIV, just as they are present for HIV-negative women.
Keywords: Body image; HIV; Women; Feminist; Narrative; Postmodern; Social Work; Social Work